Adorable knitted animals : cute stuffed toys to knit the Japanese way - Ibuki, Hiroko (Tuttle Publishing, 2021)
Sweet and soft animal friends made with popular Japanese knitting techniques. This collection of 25 cuddly toy animals includes everything from favourite pets to zoo animals. Made with soft materials and adorable expressions, these sweet companions make the perfect gift for newborns, grandchildren and animal lovers alike. While some fit in the palm of your hand, the largest is the huggable size of 16 inches (40 cm). The knitted animal projects in this book include: Beatrix the Rabbit William the Penguin Mimi the Japanese Dormouse Winston the Sloth Frannie the Doe Harry the Hedgehog And many more! Each animal is knitted in parts and then felted and sewn together. Detailed instructions and photos guide you through the key steps of construction, while a set of steps for executing specific stitches simplifies the process. Clear explanations of the knitting charts and symbols help you learn the basics of Japanese-style knitting. Projects should be knit with natural fibres that can be felted to achieve that perfectly cosy feel.